EFFECT OF A SPECIFIC EXERCISE PROGRAM ON THE STRENGTH AND RESISTANCE LEVELS OF LUMBAR MUSCLES IN WAREHOUSE WORKERS - Cristina Carvalho Mesquita (2012)
Objective: The aim of this study was to verify the influence of a specific exercise program on the strength and resistance levels of lumbar flexors and extensors in warehouse workers. Materials and Methods: The population used in this randomized controlled trial included 557 warehouse male workers from a food distribution company in Oporto/Portugal. Upon the application of the selection criteria, 98 workers deemed eligible were randomized in two groups: 57 were assigned to the intervention group and 41 to the control group. The intervention included 9 easily-executed exercises to promote stretching and strengthening of the lumbar region, to be executed daily, at the beginning of the working time, at the company facilities and lasting 8'. Trunk muscles' voluntary strength and resistance were measured using an isometric electronic dynamometer (Globus Ergometer, Globus, Codigne, Italy) at baseline and eleven months after implementing the exercise program. The data was analyzed using SPSS (R), version 17.0. Results: After implementation of the exercise program, in the intervention group, all variables increased, significant differences were observed as for the muscle strength and resistance values (p = 0.014 and p = 0.006, respectively), as well as in the ratio extensors/flexors (p = 0.037). In the control group, all variables decreased, with a statistically significant decrease of the trunk flexors strength level (p = 0.009). Conclusion: The results of this study suggest that a specific exercise intervention program can increase trunk extensors strength and resistance.